Que pensent et disent des adolescents sur la pratique de la philosophie et ses apports? - Anda Fournel; Mathieu Gagnon; Olivier Michaud; Jean-Pascal Simon
We propose to deepen the understanding how youth perceive philosophy practices. What is philosophy for them? What benefits and learning do they perceive from it, both in school and in life in general? Collecting data on these questions seems crucial if we want to examine whether and to what extent this practice meets the expectations rooted in it. In this sense, our proposal aims to question the ambitions and achievements by adopting the descriptive and clear-eyed postures mentioned in the dossier. To answer these questions, we propose a qualitative analysis of a corpus of recorded interviews with students from Quebec (16-17 years old) and France (11-14 years old). We have observed common points: students agree on a social dimension of the practice, describing it as a process of questioning that aims at deepening ideas and understanding others' points of view. However, differences emerge in how they conceive the benefits according to the contexts. The analysis shows that some challenges remain to optimize the benefits of philosophical practices for students.